Potential Interaction of Fresh Garlic with Metformin during Ischemia-Reperfusion Induced Cardiac Injury in Diabetic Rats. (6th September 2021) - Asdaq, Syed Mohammed Basheeruddin; Lokaraja, S.; Alamri, Abdulhakeem S.; Alsanie, Walaa F.; Alhomrani, Majid; Almutiri, Abdulrahman Hadi; Nagaraja, Sreeharsha; Imran, Mohd
Abstract : Background and objectives . Diabetes mellitus is a metabolic illness related to numerous organ damage, dysfunctions, and renal malfunction. In diabetes, oxidative stress plays a crucial part in the biochemical and pathological alterations linked to myocardial ischemia-reperfusion injury (IRI). In this study, an effort was made to evaluate the possible interaction of garlic (A llium sativum) (250 mg/kg) with the biguanide derivative, metformin (MET) (70 mg/kg), on IRI induced myocardial dysfunction in the isolated rat heart. Methods . The study was undertaken on both normoglycemic and alloxan (90 mg/kg) induced diabetic Sprague Dawley rats weighing 150–250 g. At the completion of the treatment phase (30 days for garlic, 250 mg/kg, oral; 10 days for MET, 70 mg/kg, oral), rats were anesthetized and mounted on the modified Langendorff's apparatus. IRI was produced by myocardial no-flow global ischemia. Developed tension (DT) and heart rate (HR) were recorded both before and after ischemia. The perfusate was collected to estimate the leakage of cardiac biomarkers (Creatine Kinase-MB: CK-MB and Lactate dehydrogenase: LDH). Hearts were removed from the setup and utilized to prepare heart tissue homogenate (HTH) and histological slides. The endogenous antioxidants, superoxide dismutase (SOD) and catalase (CAT), in addition to oxidative thiobarbituric acid substances (TBS), were estimated in HTH. Results . The hemodynamic parameters, including percentage recovery in HR and DT, were found significantly higher in animals pretreated with garlic and MET in diabetic rats (DR). Both SOD and CAT enzyme activities increased significantly while TBS levels were reduced in the HTH of animals treated with garlic and MET. The cardiac markers CK-MB and LDH levels also increased in HTH with a corresponding decrease in the perfusate. The histopathological changes in the heart and pancreas demonstrated noticeable protection of the tissues due to pretreatment with garlic and MET. Taken together, these findings advocate that reactive oxygen species derived from hyperglycemia execute an important function in myocardial global IRI; the therapy of garlic homogenate was found to be effective in alleviating these toxic effects. Conclusion . The combined therapy of MET and garlic provided synergistic cardioprotection, implying that garlic seems to possess promise in lowering toxic parameters by protecting diabetic induced myocardial injury.